Anticancer Water‐Soluble Organoruthenium Complexes: Synthesis and Preclinical Evaluation - Azmanova, Maria; Rafols, Laia; Cooper, Patricia A.; Seaton, Colin C.; Shnyder, Steven D.; Pitto‐Barry, Anaïs (Chembiochem : a European journal of chemical biology, 2022)
The synthesis, characterisation, and evaluation of the in vitro cytotoxicity of five maleonitriledithiolate‐based ruthenium metal complexes bearing various phosphine ligands towards two ovarian cancer cell lines (A2780 and A2780cisR), one non‐small‐cell lung cancer cell line (H460) and one normal prostate cell line (PNT2) are presented herein. These 18‐electron complexes were designed with four water‐soluble phosphine ligands to increase the water‐solubility character of the corresponding electron‐deficient ruthenium complex which showed great in vitro promises, and triphenylphosphine for comparison. The complexes with triphenylphosphine‐3,3′,3′′‐trisulfonic acid and triphenylphosphine present similar cytotoxicity compared to the 16‐electron precursor, with equal cytotoxicity to both A2780 and A2780cisR. Hints at the mechanism of action suggest an apoptotic pathway based on reactive oxygen species (ROS) production. No toxicity was observed in preliminary in vivo pilot studies for these two complexes in subcutaneous A2780 and A2780cisR xenograft models, with some evidence of tumour growth delay. Phosphine ligands are coordinated to [(η6‐p‐cymene)Ru(maleonitriledithiolate)] to obtain ruthenium(II) complexes with different hydrophilicities. Characterisation and evaluation of the in vitro cytotoxicity towards two ovarian, one non‐small‐cell lung cancer cell lines and one normal prostate cell line are presented. A mechanism of action based on reactive oxygen species production leading to apoptosis is suggested. In vivo evaluation suggests some evidence of tumour growth delay.